2017
DOI: 10.1038/s41598-017-02177-2
|View full text |Cite
|
Sign up to set email alerts
|

Re-exposure to nicotine-associated context from adolescence enhances alcohol intake in adulthood

Abstract: Alcohol and nicotine are the two most commonly-abused substances and are often used together. Nicotine enhances alcohol-drinking behaviors in humans and in animals, and was suggested to enhance the reinforcing properties of other reinforcers. Here, we show that nicotine-associated environment, rather than nicotine itself, enhances alcohol intake in rats. Adolescent rats received repeated intermittent injections of nicotine (0.4 mg/kg, i.p., 5 injections, every 3rd day) or saline. The injection was paired with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The dorsal striatum is divided into two anatomical and functional subregions: the DMS and the DLS. The DMS is implicated in goal-directed behavior (Yin et al, 2005;Yin and Knowlton, 2006) and is important for the early stages of alcohol consumption (Corbit et al, 2012). The DLS is implicated in habit learning .…”
Section: The Effect Of Excessive Alcohol Consumption On Fgf2 Expressimentioning
confidence: 99%
See 1 more Smart Citation
“…The dorsal striatum is divided into two anatomical and functional subregions: the DMS and the DLS. The DMS is implicated in goal-directed behavior (Yin et al, 2005;Yin and Knowlton, 2006) and is important for the early stages of alcohol consumption (Corbit et al, 2012). The DLS is implicated in habit learning .…”
Section: The Effect Of Excessive Alcohol Consumption On Fgf2 Expressimentioning
confidence: 99%
“…*p Ͻ 0.05; # p ϭ 0.09. (White and McDonald, 2002;Featherstone and McDonald, 2004;Yin et al, 2004) and in compulsive alcohol/drug consumption (Everitt and Robbins, 2005;Corbit et al, 2012). Because we found that excessive voluntary alcohol intake led to upregulation of Fgf2 expression in the dorsal striatum (Fig.…”
Section: The Effect Of Excessive Alcohol Consumption On Fgf2 Expressimentioning
confidence: 99%
“…Adnp expression was normalized to Gapdh expression [7,8,29]. Importantly, we recently showed that Gapdh levels are not affected in mice under the alcohol drinking protocols used here [7].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were euthanized, and brains were quickly removed and placed on an ice-cold platform. Tissues from the NAc, dorsal hippocampus and VTA were carefully dissected from 1-mm slices using a brain matrix and immediately snap-frozen in liquid nitrogen and stored at −80°C until use for further analysis for qRT-PCR, as previously described [7,29].…”
Section: Tissue Collectionmentioning
confidence: 99%
“…Interestingly, a recent study showed that the reexposure to a context previously associated with nicotine caused a 50 percent reduction in Gdnf expression in the VTA, coupled with pronounced and long-lasting (3 month) increases in operant alcohol selfadministration and relapse (Zipori et al 2017). These findings suggest that breakdown of the GDNF pathway is a common adaptation that may underlie co-morbidity of nicotine and alcohol misuse.…”
Section: Gdnf Is a Negative Regulator Of Alcohol Intakementioning
confidence: 99%